RELIABILITAS DAN VALIDITAS INDIKATOR KETAHANAN KELUARGA DI INDONESIA - Herien Puspitawati; Tien Herawati; Ma'mun Sarma (Jurnal Kependudukan Indonesia, 2018)
Family resilience is needed to support its members to face challenges and prevent them from risks of the problems around them. Although the concept of family resilience has been mentioned in Law No. 52/2009 on Population Growth and Family Development, universal indicators to understand the level of family resilience have not been available yet. This study aims to (i) analyze the category of family resilience between intact and single families; (ii) test the reliability and validity of family resilience indicators; and (iii) examine the effect of family structure towards family resilience. This paper used data from the study of the Ministry of Women Empowerment and Child Protection in collaboration with the Center for Gender and Children's Studies LPPM-IPB in 2015 in Bogor Regency. Reliability and validity tests indicate family resilience indicators that used in this study are reliable and valid. Also, intact families is more resilient than single families, both of each component and in total. These findings indicate the significant effect of family structure on total family resilience. Future research is recommended to test the validation of a broader scope of family resilience indicators that look at the different demographic and socio-economic conditions of the regions.